CORPORATE GOVERNANCE DAN PENGUNGKAPAN LINGKUNGAN BERDASARKAN ISO 14001 DI INDONESIA - Sri Supatminingsih (Jurnal Akuntansi dan Pajak, 2015)
The purposes of this study were determine the level of environmental disclosure in Indonesia, examining differences in the level of environmental disclosure in ISO 14001 certified company between service firms and manufacturing companies. The study also examines the effect of corporate governance on environmental disclosure. Corporate governance is proxied as the number of commissioners, the proportion of independent commissioners, the number of commissioners meeting, the number of audit committee members, the proportion of independent audit committee members, and the number of audit committee meetings. In this study, firm size and industry type are used as control variables. Environmental disclosure is measured by the elements of ISO 14001. The sample in this study 60 companies certified ISO 14001 and 60 companies non certified ISO 14001 listed in the Indonesia Stock Exchange (BEI) in 2009 and 2010. Sample selection is done by purposive sampling. Technical analysis is a classic assumption test, descriptive statistics and hypothesis testing using multiple regression, t-test, and Annova. The results showed the average environmental disclosures in Indonesia amounted to 60.71% for companies that certified ISO 14001 and 25.98% for companies that non certified ISO 14001. There are differences in the level of disclosure in the company's ISO 14001 certified between service firms and manufacturing companies. Based on test results using 0.05 significance level variables were significant positive effect on environmental disclosure is the proportion of independent audit committee. Control variables firm size and industry type on disclosure of environmental impact at the level of 10%.Key word : corporate governance, board of commissioners, audit committee, environmental disclosure.